DIRECTIVE ILLOCUTIONARY ACTS FOUND IN "PETER PAN & WENDY" MOVIE - Ni Kadek Linda Elpiani; Ni Wayan Suastini (Yavana Bhasha : Journal of English Language Education, 2024)
This research looked at the film Peter Pan and Wendy's directive illocutionary acts. It assesses how all of the characters in the film convey directive illocutionary acts. The purpose of this research is to identify the various sorts of directive illocutionary acts. The observation method was used to acquire the data. The data is acquired by watching the film several times while reading the transcript and recognizing the statements that contained directive illocutionary acts. This study employed the qualitative method to analyze the data using Kreidler's (1998) theory, divide the utterance of the directive illocutionary act into three categories: command, request, and suggestions. As a result, this research discovered all forms of directed illocutionary acts according to Kreidler's (1998) theory. There were 86 data found, with command being the most common sort of directive illocutionary act occurring with 61 data, request having 19 data, and suggestion having 6 data.